Caracterização da pesca artesanal e interação com tartarugas marinhas no município de Areia Branca/Rio Grande do Norte/Brasil - Saldanha, Angela Thais Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
In Brazil, fishing facilitates its growth, with social inclusion and generation of employment and income. In the state of Rio Grande do Norte, artisanal fishing is an important source of income and food for coastal populations, but has been a source of impact on the marine biota. In the Costa Blanca / RN region there are reports of incidental catches of sea turtles, with trapping in fishing nets. The objective of this work was to characterize fishing, to investigate its interactions with sea turtles in the city of Areia Branca / RN, and to contribute to its conservation and preservation. Specifically outline the profile of the fishermen and characterize the fishing activity. For this, interviews were conducted with fishermen, through a questionnaire related to fishing. 32 fishermen were interviewed. The fishing activity was carried out in its totality by men, with more frequency of age (33%) between 51 and 60 years. The experience with fishing ranged from 2 to 48 years, with an average of 28 years of dedication. On the educational level 31.25% of the fishermen were not literate, 18.75% had incomplete secondary education and only 3.13% were able to finish the average level. Artisanal fishing had great importance in the family budget for 84.38% of fishermen, who used fish, both for family consumption and for income generation. A variation of the "vai viene" type fishery was observed. The most frequent fisheries were those carried out between 15 and 30 days. The workday ranged from 3 to more than 7 hours / day. The majority (62.50%) of the fisheries lasted more than 7 hours / day. A percentage of 62.96% of the fishermen used Areia Branca as a fishing area and 51.85% of them highlighted the summer as the best time for fishing. The fishing fleet consisted of small and medium-sized motorized vessels. A percentage of 33.33% of the fishermen were boat owners. The most used types of vessels were boats, with a frequency of (43.75%), with 1 and 4-cylinder engines and fish storage capacity of up to 10 tonnes. The main fishing gear used were netting, line and hook, trammel net, trawl net, fishing pole and manzuá. The most captured species were Guarajuba, Ariacó, Atum, Serra, Cavala and Dourado. For fish conservation, the majority of fishermen (42.85%) used vessels with basement, with ice and canvas. The sale of frozen fish in (50%) of the cases and the transfer of the fish to the fisherman prevailed. Regarding the conflicts, the fishermen referred to the Inspection of IBAMA, the presence of Seismic Survey Ships in the Region and of Foreign Boats. Among the fishermen interviewed, 88.89% affirmed the presence of sea turtles at sea and 95.83% of them reportedly happened while fishing, beached or killed. Five species were identified green turtle, leather turtle, comb turtle, loggerhead turtle and olive. According to reports from the fishermen interviewed, 25.93% of them have already caught sea turtles, often 1 to 3 times a year. A percentage of 62.96% of fishermen reported no longer use these animals as food. Approximately 50% of fishermen suggested that the most appropriate strategies for the conservation of sea turtles would be to avoid the use of coarse-grained nets, fishing, where there are the largest occurrences of sea turtles and a ban on the use of nets, such as fishing, since gill nets are indicated as the most interrelatable fishing gear with sea turtles. In Areia Branca it is clear the existence of the interaction between the fishing with net of waiting and the accidental capture of sea turtles and the artisanal fishing represents one of the main economic activities for the Municipality, besides being of fundamental social and economic importance for the artisanal fishermen.
Monografia
Keywords: Atividade pesqueira; Quelônios; Captura acidental; Conservação; Fishing activity; Chelonians; Accidental capture; Conservation; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA